2021
DOI: 10.1097/wnr.0000000000001723
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of brain c-Fos expression in response to feeding behavior in acute and chronic inflammatory pain condition

Abstract: Objectives Feeding behavior is known to have potential to alleviate pain. We recently demonstrated that both 24 h fasting and 2 h refeeding (food intake after 24 h fasting) induce analgesia in inflammatory pain conditions via different brain mechanisms. However, brain structures that distinctly involved fasting-and refeeding-induced analgesia is still unknown. Hence, this study is aimed to reveal brain structures mediating fasting-and refeedinginduced analgesia.Methods Mice were given intraplantar (i.pl.) inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…c‐Fos expression was also used to verify the alteration of ALFF‐nominated brain areas and find abnormal neuronal activity. c‐Fos expression has previously been found to have significant upregulation in the frontal cortex, the third ventricle, hippocampus, and the spinal nucleus of the trigeminal nerve in the medulla after menthol‐stimulated corneal pain in rabbits 20,21 . In line with the rs‐fMRI results, the upregulated mount of c‐Fos verified the abnormal neuronal activity, especially in S2, AID, AIP, AuV, TeA, and Ect in corneal neuropathic pain mice.…”
Section: Discussionsupporting
confidence: 76%
“…c‐Fos expression was also used to verify the alteration of ALFF‐nominated brain areas and find abnormal neuronal activity. c‐Fos expression has previously been found to have significant upregulation in the frontal cortex, the third ventricle, hippocampus, and the spinal nucleus of the trigeminal nerve in the medulla after menthol‐stimulated corneal pain in rabbits 20,21 . In line with the rs‐fMRI results, the upregulated mount of c‐Fos verified the abnormal neuronal activity, especially in S2, AID, AIP, AuV, TeA, and Ect in corneal neuropathic pain mice.…”
Section: Discussionsupporting
confidence: 76%
“…However, we do not exclude the possibility that other brain regions may also be participated in the refeeding-induced analgesia, as numerous brain regions interact to process pain and feeding behavior [57,58]. Indeed, the whole brain c-Fos analysis shows possible involvement of other brain regions such as the basolateral amygdala, medial prefrontal cortex, lateral parabrachial nucleus, and ventromedial hypothalamus [59]. Future studies of different brain regions will further help us to understand the cellular mechanisms and brain circuits for refeeding-induced analgesia.…”
Section: Discussionmentioning
confidence: 95%
“…Findings have demonstrated that pain relief increased c-Fos expression in the NAc and induced dopamine release in the NAc under acute inflammatory pain conditions. 52,53 In this study, anterograde and retrograde tracing studies demonstrated that VTA dopaminergic neurons were also found to directly project to the CeA. Although there were fewer of these projections than of those projecting to the NAc, we could not exclude a key role for amygdala-projected dopaminergic signaling in pain relief and the affective dimension of pain.…”
Section: Discussionmentioning
confidence: 68%